1986
DOI: 10.1364/ol.11.000224
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative chirping of laser pulses shorter than 100 fsec in a saturable absorber

Abstract: We present a calculation of the chirp generated in laser pulses shorter than 100 fsec on propagation through a saturable absorber (DODCI in ethylene glycol). The calculation takes into account the absorber saturation and the solvent nonlinear refractive index. At pulse energies greater than 10 nJ the chirp tends to be predominantly positive, and it increases rapidly as the pulse duration becomes shorter than 50 fsec. At pulse energies in the 1-7-nJ range the chirp is mostly negative for pulses longer than 30 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…In this paper we report that, by the change of the incident angle to cavity mirrors instead of the exchange of mirrors in the last technique, up-chirp can be compensated. In addition, it is shown that the amount of the second-order dispersion obtained for the up-chirp compensation agrees well with a recent analytic result of chirp behaviors due to intracavity self-phase modulation [ 5 ] . Furthermore, the influence of the third-order disper- sion due to mirrors at the optimum amount of the secondorder dispersion on femtosecond pulses is estimated.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In this paper we report that, by the change of the incident angle to cavity mirrors instead of the exchange of mirrors in the last technique, up-chirp can be compensated. In addition, it is shown that the amount of the second-order dispersion obtained for the up-chirp compensation agrees well with a recent analytic result of chirp behaviors due to intracavity self-phase modulation [ 5 ] . Furthermore, the influence of the third-order disper- sion due to mirrors at the optimum amount of the secondorder dispersion on femtosecond pulses is estimated.…”
supporting
confidence: 86%
“…Miranda et al carried out a simplified analysis of frequency-chirp C ( t ) = daw ( t ) / d t imposed on femtosecond pulses interacting with a saturable absorber including the effect of nonlinear refractive index due to the solvent [5]. Their results showed that the chirp in a CPM laser remarkably depends on the intracavity pulse energy E,,.…”
mentioning
confidence: 99%
“…In contrast, in the SA section, the refractive index decreases as the absorption saturates [18]. Because the frequency shift increases with the degree of absorption saturation [19], this can balance the negative intracavity GVD. In the model of the saturation dynamics [19], the nonzero phase-relaxation time of the SA, T2, was not included assuming that pulse durations were longer than T2.…”
Section: Discussionmentioning
confidence: 99%
“…Because the frequency shift increases with the degree of absorption saturation [19], this can balance the negative intracavity GVD. In the model of the saturation dynamics [19], the nonzero phase-relaxation time of the SA, T2, was not included assuming that pulse durations were longer than T2. The carrier-carrier scattering time in GaN is reported to be less than 15 fs [20], so that the saturation dynamics in the SA can be applied to explain the frequency shift.…”
Section: Discussionmentioning
confidence: 99%
“…In this Letter we demonstrate that the addition of high-NRI organic materials to a solution of the saturable absorber permits intracavity pulse compression in a simple CPM laser employing cavity-mirror dispersion adjustment. The NRI organic materials used have the following properties: (1) a higher NRI than that of the EG solution (n 2 = 3.0 X 10-16 cm 2 /W), 4 ' 9 (2) an ultrafast time-dependent index change by electronic hyperpolarizability, (3) high solubility for EG or a mixture of EG and benzylalcohol, (4) no absorption around the lasing wavelength region, and (5) good photochemical stability in the solution. Recent studies of high-NRI organic materials enabled us to find suitable materials that satisfy these properties.…”
mentioning
confidence: 99%